2019
DOI: 10.1002/adma.201902432
|View full text |Cite
|
Sign up to set email alerts
|

Fast Gelation of Ti3C2Tx MXene Initiated by Metal Ions

Abstract: Graphene faces the same problem, but its self-assembly into a 3D structures can effectively solve these problems. [5,6] The gelation of graphene oxide (GO) is the mostly used method to prepare a 3D assembled structure, and this process is triggered by the surface chemistry changes of GO NSs in solution. However, the gelation of the other 2D materials, such as transition metal dichalcogenides (TMDs), transition metal oxides (TMOs), and h-BN, [7][8][9][10] is difficult to achieve because of the fewer functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
298
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(330 citation statements)
references
References 34 publications
(38 reference statements)
5
298
0
Order By: Relevance
“…One of the first concerns with the assembly of MXene architectures is their weak gelation capability (see GO) [54], which reduces the connections between sheets and hinders their mechanical stability. Therefore, if the concentration is too low, for example, a freeze-dried MXene colloid collapses into a powder of aerogel-like porous particles [53].…”
Section: Assembly By Induced Gelationmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the first concerns with the assembly of MXene architectures is their weak gelation capability (see GO) [54], which reduces the connections between sheets and hinders their mechanical stability. Therefore, if the concentration is too low, for example, a freeze-dried MXene colloid collapses into a powder of aerogel-like porous particles [53].…”
Section: Assembly By Induced Gelationmentioning
confidence: 99%
“…Therefore, if the concentration is too low, for example, a freeze-dried MXene colloid collapses into a powder of aerogel-like porous particles [53]. To overcome this problem, additives such as ethylenediamine (EDA) [55], thiourea dioxide (thiox) and ammonia [56], PAA [57], and divalent metal ions [54], have been used to functionalize the Ti 3 C 2 T x sheets and enhance their interconnectivity during the gelation process [54][55][56][57]. The mechanism that induces gelation depends on the additive used and can be via a chemical reduction of the surface of the sheets (when using mild reducing agents, such as EDA, thiox and ammonia, or PAA), or simple electrostatic interactions of the surface functional groups and the cross-linking agent (e.g.…”
Section: Assembly By Induced Gelationmentioning
confidence: 99%
See 1 more Smart Citation
“…prepared a 3 D N‐doped graphene framework which generated a high specific capacitance in supercapacitors and also displayed an obvious electrocatalytic activity for ORR . Aside from graphene, recent reports have shown that MXenes can also been assembled to form 3 D architectures . Deng et al.…”
Section: Applications Of 2 D Materials In Electrochemical Energy Storagementioning
confidence: 99%
“…To date, various2Dm aterials have been tested in supercapacitors, owing to their suitable physicochemical properties. [56] Amongt hem, graphene-based materials have drawn extensive attention. [57] They can be used as active materials directly in EDLCs owing to their large specific surfacea rea and high conductivity.…”
Section: Supercapacitorsmentioning
confidence: 99%